Communication Model of Islamic Religious Extenders in Building a Sakinah Family in Deli Tua District - Handoko, M; Rubino, Rubino; Kustiawan, Winda (JURNAL AT-TURAS, 2022)
This study aims to analyze the communication model and implementation by Islamic Religious Counselors in Building Sakinah Families in Deli Tua District and the Barriers to Applying Islamic Religious Extension Communication Models in Building Sakinah Families in Deli Tua District. This research uses a descriptive analysis method and the approach uses a qualitative approach. Sources of data come from primary, namely through interviews, and secondary data by examining books, journals, and other documents. Based on the results of the study that the communication model used by Islamic Religious Counselors in building the Sakinah Family in the Deli Tua sub-district, namely using a two-way communication model. The two-way model applied by Islamic Religious Counselors when building a sakinah family, namely the existence of feedback. Implementation of the communication model is done by going directly to the community and interacting. The communication process is carried out with lectures accompanied by questions and answers with the community. As for the obstacles of Islamic Religious Counselors in building a sakinah family in Deli Tua District, namely, first, the presence of provocateurs to incite them not to attend the coaching to build a sakinah family, the domicile of the community being fostered are Javanese, technological stuttering, the clashing schedule of coaching with the harvest season. The solution to overcome these obstacles is to evaluate yourself on the style of speaking so that you can adjust to whom you interact with, Involve power from outside yourself, and be smart so that you get used to using non-verbal communication.